1943
DOI: 10.1001/jama.1943.02840090026008
|View full text |Cite
|
Sign up to set email alerts
|

The Placental Transmission of Protective Antibodies Against Whooping Cough

Abstract: Whooping cough is the dread contagious disease of infancy. During the first two years of life it is the cause of more deaths than measles, diphtheria, poliomyelitis and scarlet fever combined.1 Against the latter diseases the baby usually is born with a passive immunity transmitted by the mother through the placenta.2 Since this is a passive immunity it endures for only approximately six months. Such does not seem to be the case with whooping cough.Pediatrists not infrequently encounter cases of whooping cough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1949
1949
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…41 During the 1940s and 1950s small numbers of women received whole cell pertussis vaccine during the third trimester of pregnancy. [59][60][61][62] No adverse events were documented and increased antibody levels in mother and baby with enhanced in vitro killing of B. pertussis were reported. Concerns that high maternal antibody levels would suppress infant immune response to pertussis vaccines in infancy were lessened when Englund et al demonstrated that no significant interference occurred with DTaP vaccines.…”
Section: Immune Response Following Pertussis Immunization In Pregnancymentioning
confidence: 99%
“…41 During the 1940s and 1950s small numbers of women received whole cell pertussis vaccine during the third trimester of pregnancy. [59][60][61][62] No adverse events were documented and increased antibody levels in mother and baby with enhanced in vitro killing of B. pertussis were reported. Concerns that high maternal antibody levels would suppress infant immune response to pertussis vaccines in infancy were lessened when Englund et al demonstrated that no significant interference occurred with DTaP vaccines.…”
Section: Immune Response Following Pertussis Immunization In Pregnancymentioning
confidence: 99%
“…The possibility of protecting newborns against pertussis by immunizing their mothers during pregnancy has been under investigation since the 1930s (33). In fact, maternal immunization increased the concentrations of pertussis antibodies in infants to as much as 100% of the maternal titers (11,31,33) and babies born to immunized mothers had 2.9 times greater levels of specific antibodies to B. pertussis compared to babies born to nonimmunized mothers (31). Therefore, it would be advantageous to immunize pregnant women with appropriate pertussis antigens to provide better passive immunity to their infants (28).…”
mentioning
confidence: 99%
“…Studies with mice, the most commonly used model of pertussis, demonstrated a protective role for maternal immunity following a challenge with B. pertussis (11). However, this model has its limitations in its similarity to humans and limited access to samples such as cells, saliva, serum, colostrum, milk, and bronchoalveolar lavage (BAL) fluid.…”
mentioning
confidence: 99%
“…In 1941, the Milwaukee Health Department began to record deaths from whooping cough by age in months. An analysis of 34 deaths occurring in the entire city of Milwaukee for the years 1941 to 1948, inclusive, as shown in figure 3, reveals that 8 deaths (23.8 per cent) occurred in infants under 3 months, 13 (38.2 per cent) in infants under 4 months, 17 The mortality rate in children hospitalized at South View Hospital is seen to be over seven and a half times as great in those under 1 year of age as in those over 1 year old, with 52.8 per cent of the deaths occurring in infants under 6 months of age. Furthermore, citywide mortality statistics do not vary greatly from those of the hospital.…”
Section: Review Of the Literature On Prophylaxismentioning
confidence: 99%